Insights into Acute Ischemic Stroke Prognostic Factors in Patients with Mechanical Heart Valves - Jorge Miguel Moreira Bezerra (2022)
Background and purpose: Patients with Mechanical Heart Valves (MHV) are at greater risk of having an Acute Ischemic Stroke (IS). However, prognostic factors of these patients are not well-defined. We aimed to identify factors associated with mortality, thromboembolic and hemorrhagic events at 2 years after IS in these patients. Material and Methods: In this single-center retrospective observational study, we assessed clinical, laboratory and imaging data at admission, during internment, and follow-up of patients with MHV that presented with an IS in a comprehensive Stroke Unit, between January 2008 and December 2019. Patients were followed-up for 2 years after IS and mortality, thromboembolic and hemorrhagic events were recorded. Univariate and multivariate logistic regression analysis were performed to assess the association between potential predictors and outcomes by logistic regression. Results: Sixty-three patients were included. In multivariate analysis, mortality was associated with higher uric acid at admission (Odds Ratio (OR)=2.283, 95% Confidence Interval (CI) 1.242 to 4.197, p=0.008), National Institutes of Health Stroke Scale (NIHSS) at 24 hours (OR=1.192, 95% CI 1.037 to 1.370, p=0.013) and at discharge (OR=1.231, 95% CI 1.048 to 1.446, p=0.011), and modified Rankin Scale at 3 months (OR=3.468, 95% CI 1.306 to 9.207, p=0.005). Major hemorrhagic events were associated with lower ASPECTS at admission (OR=0.612, 95% CI 0.383 to 0.977, p=0.040), higher NIHSS at 24 hours (OR=1.160, 95% CI 1.016 to 1.323, p=0.028), and restarting anticoagulation more than one day after IS (OR=16.073, 95% CI 3.047 to 84.773, p=0.001). Thromboembolic events were not associated with any of the evaluated factors. Conclusion: A range of parameters are available to identify patients at greater risk of death and other complications in the 2 years after IS, providing essential information regarding prognosis.